A novel import route for an N‐anchor mitochondrial outer membrane protein aided by the TIM23 complex. (29th April 2014) - Song, Jiyao; Tamura, Yasushi; Yoshihisa, Tohru; Endo, Toshiya
Abstract The membrane topology of Om45 in the yeast mitochondrial outer membrane (OM) is under debate. Here, we confirm that Om45 is anchored to the OM from the intermembrane space (IMS) by its N‐terminal hydrophobic segment. We show that import of Om45 requires the presequence receptors, Tom20 and Tom22, and the import channel of Tom40. Unlike any of the known OM proteins, Om45 import requires the TIM23 complex in the inner membrane, a translocator for presequence‐containing proteins, and the membrane potential (ΔΨ). Therefore, Om45 is anchored to the OM via the IMS by a novel import pathway involving the TIM23 complex.